BODY MASS INDEX STATUS WITH HYPERTENSION - Tri hardi Miftahul Ulum; Liza Novitasari Wijaya (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2023)
Hypertension is the leading cause of premature death in the world. It does not only attack the productive age but also attacks the elderly. Hypertension is known as "The Silent Killer" because it is often without complaints and there are complications. Body Mass Index (BMI) is very influential on blood pressure. Abnormal BMI has twice the chance of experiencing hypertension and triggers higher risk factors for hypertension than normal people. This research aims to determine the relationship between BMI and the incidence of hypertension in Ngablak Hamlet, Sitimulyo Piyungan Village, Bantul, Yogyakarta. This research was an analytic observational study with a cross-sectional research design. Sampling used the Accidental Sampling technique with 30 respondents based on the inclusion and exclusion criteria. Measuring instruments used to collect BMI data were weight scales and height measuring devices (cm) and measuring instruments used to measure blood pressure are stethoscopes and sphygmomannometers. Measurements consisted of systolic and diastolic blood pressure, weight, and height. Data were analyzed using the Statistical Package for the Social Sciences (SPSS) 16.0 program. The results of this research showed a significance value of 0.044 (p <0.05). thus, there was a significant relationship between BMI and the incidence of hypertension in Ngablak Hamlet, Sitimulyo Piyungan Village, Bantul Yogyakarta.